TEACHERS’ PERCEPTION OF A FEMALE MANAGER LEADERSHIP STYLE - Aghni, Luluk Aulia (Global Expert: Jurnal Bahasa dan Sastra, 2023)
The most important part of an organization, an institution or a school is the leadership and the person who did it called the leader. The leader is someone who can give big influence and also inspire the subordinate. Leadership is people-driven and the ability to inspire people helps to achieve the set goals of an organization (Lahti, 2013). Most of organization is sometimes lead by a male leader. Only a few that leads by the female leader. People believe that male is better than female in leading an organization. Kuchynkova (2015) reported that men tend to be more logical and rational with the requisite toughness, while women are more intuitive, sensitive and predisposed towards change and diplomacy. The writer conducted a descriptive qualitative study for this mini research. This study was conducted in order to get the teacher’s perception of female manager leadership style.